Accounting Treatment In Increasing Accountability And Transparency Of Budget Management With The Concept Of Value For Money: Perlakuan Akuntansi dalam Meningkatkan Akuntabilitas dan Transparansi Pengelolaan Anggaran Dengan Konsep Value for Money - Devi Riza Umami; Heri Widodo (Universitas Muhammadiyah Sidoarjo, 2021)
This research aims to determine the accounting treatment in increasing accountability and transparency of budget management with the concept of Value for Money in Gelang Village. This type of research is a qualitative research that uses data collection methods through interview, documentation, and observation. Types and sources of data using primary data and secobdary data. The technique of determining the informants in this study uses a purposive sampling technique, which means that the technique is intented to select informants according to the object under study. The results of the study indicate that the management of APBDes in Gelang Village has carried out a system of planning, implementation, administration, reporting, and accountability according to the rules. The application of the concept of Value for Money in budget management has been implemented through the 3E (Economy, Efficiency, and Effectiveness) well in Gelang Village. It can also be said to be transparent, because the village government has realized the APBDes funds by placing the APBDes realization report in front of the village office and holding a village meeting to discuss the APBDes program development plan